ANALISIS FAKTOR RENDAHNYA MOTIVASI BELAJAR SISWA DALAM MATA PELAJARAN IPA DI SEKOLAH DASAR - Sari, Ultari Amanda; Nadiroha, Widia; Adrias, Adrias; Syam, Salmaini Safitri (Natural Science Education Research, 2025)
The purpose of this study is to identify the factors that contribute to low motivation to learn among students in the subject of Science (IPA) in Elementary School. The research method used is qualitative literature research by analyzing various written sources, such as journals, books, and research reports. The results show that low student motivation to learn is influenced by both intrinsic and extrinsic factors. Important intrinsic factors include a lack of confidence among students, difficulty in understanding scientific concepts that are considered abstract, and low curiosity about the learning material. Extrinsic factors include monotonous and uninteresting teaching methods, limited learning facilities and infrastructure, and lack of support from teachers and parents. This study recommends the use of innovative teaching methods such as project-based learning, inquiry-based learning, and the STEM (Science, Technology, Engineering, and Mathematics) approach to motivate students. In addition, active support from teachers and parents in providing feedback and appreciation is important to increase students’ confidence and motivation in learning science.